Work Accident Reduction Strategies With Job Safety Analysis at the Gum Rosin and Turpentine Factory - Zati Hulwani Mindandi; Irwan Iftadi (Teknoin, 2023)
The production methods at the Gum Rosin and Turpentine XYZ Factory involve several types of machinery and chemicals that might result in workplace accidents. Although the most recent Job Safety Analysis (JSA) was completed in 2018, various changes in work responsibilities have resulted in complaints from melting station workers in the case of eye irritation caused by turpentine vapor exposure and PGT waste workers as having the possibility of splashes from industrial waste. The purpose of this research is to assemble the most recent JSA document to eliminate potential dangers. This research was organized into four parts. The first stage involves conducting firsthand observations to describe the workers' responsibilities at each station. The second step includes interviewing the HSE staff and supervisors to determine the possible dangers of each operation. The third stage involves consulting with the HSE supervisor to decide on precautions to minimize possible dangers. The fourth stage consists of collecting JSA papers for each station. A total of 18 job descriptions with four categories of hazards were discovered based on the assembled JSA, including physical, chemical, mechanical, and ergonomic risks. Workplace safety recommendations here include the placement of safety signs, the installation of guardrails for waste tanks, and the application of personal protective equipment.